Riccardo Migliari, Marco Fasolo. (2022). Prospettiva. Teoria e applicazioni. Milano: Hoepli (diségno, 2023)
I believe that Riccardo Migliari’s first thoughts about writing a monographic volume devoted to the ‘practice’ of perspective go back to more than ten years ago, when, while we were both attending a PRIN meeting in Turin, during an evening stroll along the Po River, he confessed to me that he had in mind an editorial project for the near future: that of wanting to devote himself, once his university commitments were over, to the writing of a monographic text devoted to this method of representation, free from academic constraints and capable of extending the study of its applications, even the more heterodox ones (such as anamorphosis or solid perspective) to other figurative practices, bordering and seemingly extraneous to architectural practices de jure. [read more]